Figure 3 from: Eberhardt U, Beker HJ, Borgen T, Knudsen H, Schütz N, Elborne SA (2021) A survey of Hebeloma (Hymenogastraceae) in Greenland. MycoKeys 79: 17-118. https://doi.org/10.3897/mycokeys.79.63363 - Eberhardt, Ursula; Beker, Henry J.; Borgen, Torbjørn; Knudsen, Henning; Schütz, Nicole; Elborne, Steen A. (Zenodo, 2021)
Figure 3 Pruned quasi-median networks of A the Hebeloma mesophaeum complex and BHebeloma marginatulum. Circles shared by two or more taxa or collections from two regions, from Greenland (G) or collected elsewhere, are divided according to the number of representatives for each class.